2014
DOI: 10.1089/jop.2013.0132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Safety and Intraocular Pressure–Lowering Effect of Tafluprost Ophthalmic Solution with Other Prostaglandin Ophthalmic Solutions

Abstract: Purpose: The benzalkonium chloride (BAK) content of tafluprost ophthalmic solution (Tapros Ò : tafluprost) has been reduced to balance corneal safety and preservative effectiveness (old formulation: 0.01%; new formulation: 0.001%). However, no reports have been published on its clinical effect. Therefore, we conducted a clinical research study to compare the safety of BAK-reduced tafluprost on the ocular surface with other prostaglandin ophthalmic solutions. Methods: This clinical study included 28 glaucoma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…No statistically significant differences in IOP were found following treatment switch, which is consistent with previous studies demonstrating similar IOP lowering efficacies …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No statistically significant differences in IOP were found following treatment switch, which is consistent with previous studies demonstrating similar IOP lowering efficacies …”
Section: Discussionsupporting
confidence: 91%
“…Tafluprost 0.0015% is an ophthalmic solution in which BAC concentration is recently reduced. Additionally, reduced prevalence of superficial punctate keratopathy (SPK) has been shown in a clinical comparison of tafluprost to latanoprost . In this study, we evaluated changes in the ocular surface status and IOP lowering effects of patients with POAG or OH and the presence of existing prostaglandin‐induced corneal disorders after being switched from latanoprost 0.005% to tafluprost 0.0015% ophthalmic solution.…”
Section: Introductionmentioning
confidence: 99%
“…Data from in vitro studies using human corneal epithelial cells and in vivo studies using rabbit models have revealed that BAC is the major cause of keratoepithelial disorders 14. After switching from latanoprost to a tafluprost formulation containing lower levels of BAC or to a travoprost formulation containing SofZia instead of BAC, the prevalence of SPK was found to decrease in two clinical studies 10,15. In addition, topical β-blockers, which decrease corneal sensitivity16 and the number of goblet cells in the conjunctiva,17 have also been associated with an increased risk of keratoepithelial disorders 11.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the risk of toxic effects with long-term use, preservative-free or less toxic formulations of IOP-lowering agents have been developed to reduce the risk of OSDs. Treatment with tafluprost formulations containing 0.001% BAC has been shown to result in a lower prevalence of superficial punctate keratopathy (SPK) than treatment with standard latanoprost formulations containing 0.02% BAC (Xalatan ® , Pfizer Inc., New York, NY, USA) 10. In addition, certain active ingredients such as timolol might also encourage the development of corneal epithelial disorders 11.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of epithelial permeability and autofluorescence of the cornea in patients with POAG or ocular hypertension (OH) demonstrated that removal of BAK from timolol resulted in an improvement of corneal epithelial barrier function and in a reduction of complaints [ 12 ]. On the other hand, it was reported in 75% of glaucoma patients that the superficial punctate keratopathy (SPK) scores improved by switching their glaucoma drugs (either latanoprost or travoprost) to BAK-reduced tafluprost [ 13 ]. Besides, switching therapy from BAK-preserved latanoprost to travoprost without BAK significantly reduced the frequency of SPK in POAG or OH patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%